Trade-Off Assessment between Environment and Economy for Demolition Waste in India - Kumar, M Kranti; D, Rajan (IJRDO - Journal of Mechanical And Civil Engineering, 2020)
In India, the amount of Construction and Demolition waste (C&D) generated is found to be 25-30 million tons out of which it is estimated that 40-50 kg/cu.m. generated mainly from the construction and minor renovation works and 300-500 kg/cu.m.is generated from the demolition of buildings, in this 90% of demolition waste goes to landfill which makes that land unfeasible. In the current scenario, the world is moving towards a sustainable approach due to various climate change catastrophes, thus using recycled materials to construction could be a greater advantage as it minimizes the impact of depletion of natural resources. Through the literature review, the major recyclable waste constituents during the demolition phase of buildings are identified and also ways of recycling them are studied. Two live projects of different scales are taken as case studies and the revised prices of discovered material (i.e. recycled material instead of new material) are used in the analysis of rate, for calculating the overall cost of the whole material in both projects. Usage of recycled  materials  leads  to  a  reduction  in  environmental  impact  along  with  an increased cost savings. Procedure for the usage of the found recyclable materials in the projects is discussed. Further, planned cost savings are achieved only by monitoring and controlling it, during execution. Cost savings are proved by comparing the derived price (i.e. a part of recycled materials is used instead of new materials) and the original price of the whole materials. Keywords:  Demolition waste, Recycle, Cost analysis, Cost savings